Teaching nutritional education in the initial training of nutritionists: a brief review (Research, Society and Development, 2020)
Nutritional Education is fundamental in the training of nutritionist professionals, given its pedagogical focus on modifying the eating behavior of specific individuals or groups, and its extremely important contribution to the understanding of the socio-cultural, economic and demographic phenomena that influence food. In this sense, this article sought to highlight the role of Nutrition Education teaching in the initial training of nutritionists. To this end, a bibliographical and exploratory survey was carried out on the Google Scholar databases and Catalog of Theses and Dissertations from the Coordination for the Improvement of Higher Education Personnel (CAPES), as well as books and documents related to Teaching and Nutritional Education. According to the results, it is seen that the nutritionist acts primarily as an educator, regardless of his area of activity, seeking change and maintaining healthy behavior. It has been seen that Nutritional Education, especially in practical activities, stimulates students' critical-reflective thinking, making learning based not only on the assimilation of content and later on the insertion of their practice, but also on the elaboration of their own ideas. However, it was noticed, from the analysis, that this discipline has been neglected, as it has a low workload in relation to others, not presenting substantial practical activities, in addition to being considered “light” and “funny” by most Thus, we consider that the teaching of Nutritional Education is a crucial part of the initial training of the nutritionist professional, as it acts as a stimulating factor for professional criticality and is related to interdisciplinary actions that cover the most varied areas of nutrition. Further research that shows this, given the scarcity of current studies on the subject.